小模数卵形齿轮线切割加工计算机辅助设计研究 - 夏懿; 黄文浩; 孟庆琳; 党学明; 刘庆升 (Jixie chuandong)
A method of Electrical Discharge Manufacturing （EDM） f or small size olivary gear is given in this paper. This method can beused to pos ition every tooth along the pitch circle and to calculate the coordinates of pro file. Based on the calculated profile coordinates, the NC program can be compile d to drive the EDM machine.